2001
DOI: 10.1016/s0893-133x(00)00185-8
|View full text |Cite
|
Sign up to set email alerts
|

Functional Consequences of Repeated (±)3,4-Methylenedioxymethamphetamine (MDMA) Treatment in Rhesus Monkeys

Abstract: Six rhesus monkeys were trained to stable performance on neuropsychological tests of memory, reinforcer efficacy, reaction time and bimanual motor coordination. Three monkeys were then exposed to a high-dose, short course regimen of ( Ϯ )3,4-Methylenedioxymethamphetamine (MDMA, "Ecstasy") (4 days, 10 mg/kg i.m., b.i.d.) Recreational use of the psychoactive drug ( Ϯ )3,4,-methylenedioxymethamphetamine (MDMA) has become increasingly popular over the past two decades (Peroutka 1987;Schuster et al. 1998). Althou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
65
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(70 citation statements)
references
References 41 publications
4
65
1
Order By: Relevance
“…sufficient to produce ‫ف‬ 50% reduction of the 5-HT metabolite 5-hydroxyindoleacetic acid (5-HIAA) in cerebrospinal fluid do not exhibit performance deficits in a range of cognitive domains (Taffe et al 2001). Those results were consistent with a similar investigations employing different behavioral assays in both rhesus (Frederick et al 1998) and squirrel monkeys (Winsauer et al 2002).…”
supporting
confidence: 81%
See 2 more Smart Citations
“…sufficient to produce ‫ف‬ 50% reduction of the 5-HT metabolite 5-hydroxyindoleacetic acid (5-HIAA) in cerebrospinal fluid do not exhibit performance deficits in a range of cognitive domains (Taffe et al 2001). Those results were consistent with a similar investigations employing different behavioral assays in both rhesus (Frederick et al 1998) and squirrel monkeys (Winsauer et al 2002).…”
supporting
confidence: 81%
“…Three of the monkeys were exposed to a repeated, highdose regimen of ( Ϯ )3,4-methylenedioxymethamphetamine HCl (MDMA) (4 days, 10 mg/kg i.m., b.i.d., expressed as the salt) 13 months prior to beginning of the present study as has been previously described (Taffe et al 2001). The remaining three animals were treated with vehicle injections on the same schedule and serve as control subjects.…”
Section: Mdma Exposurementioning
confidence: 99%
See 1 more Smart Citation
“…In addition, no influence of cannabis use on several conditions of ASR was observed. Previous animal data have shown that application of MDMA causes a selective and sustained reduction of 5-HT levels in the brain (Stone et al, 1986;Commins et al, 1987;Schmidt, 1987;Battaglia et al, 1988;Insel et al, 1989;Wilson et al, 1989;Ali et al, 1993;Scheffel et al, 1998;Hatzidimitriou et al, 1999;Taffe et al, 2001), and there is also some evidence for selectively lowered serotonergic neurotransmission in chronic MDMA users (McCann et al, 1994. Acute 5-HT depletion decreased PPI in animals and humans consistently (Phillips et al, 2000; Fletcher et al, Figure 2 Habituation curve diagrammed as mean amplitude of 116-dBpulse-alone trials in six blocks and a single initial 116-dB-pulse-alone trial (means7SEM).…”
Section: Resultsmentioning
confidence: 99%
“…In animals, administration of MDMA produces a rapid and marked release of serotonin (5-HT) via inhibition and reversal of the 5-HT transporter (Rudnick and Wall, 1992). There is convincing evidence that MDMA produces a substantial and sustained long-term neurotoxic loss of 5-HT nerve terminals with an associated depletion of 5-HT in several brain regions of rats, guinea pigs, and several species of nonhuman primates (Stone et al, 1986;Commins et al, 1987;Schmidt, 1987;Battaglia et al, 1988;Insel et al, 1989;Wilson et al, 1989;Ali et al, 1993;Scheffel et al, 1998;Hatzidimitriou et al, 1999;Taffe et al, 2001). Studies of MDMA use in humans have also shown selective decrements in cerebrospinal fluid (CSF) concentrations of 5-hydroxy indoleacetic acid (5-HIAA) as a marker for central serotonergic depletion, with no alterations in CSF homovanillic acid (HVA) or 3-methoxy-4-hydroxyphenylglycol (MHPG), the major metabolites of dopamine and norepinephrine, respectively (McCann et al, 1994.…”
Section: Introductionmentioning
confidence: 99%